NUCLEAR LOCALIZATION OF ARABIDOPSISˈS HEAT SHOCK FACTOR HSFA1D USING BIMOLECULAR FLORESCENCE COMPLEMENTATION (BIFC) SYSTEM - Z. Shah; G S. Ali; A. El-Sayed; M. Hussain; H. Shah; M. Z. Ahmad; N. Ahmad 1and A. Iqbal (Journal of Animal and Plant Sciences, 2020)
Response to thermal stress in plants is mostly regulated by heat shock factors (hsfs). Among hsfs, HsfA1d is one of the key players in protecting plants against heat stress. Subcellular localization of gene is prerequisite for its characterization. Bimolecular Fluorescent Complementation (BiFC) provides the most advance and reliable tool to visualize protein-protein interactions and to explore their location in living system. Objective of the present study was to accomplish sub cellular localization of HsfA1d by using BiFC. HsfA1d was cloned in-frame with complementary halves of yellow florescent proteins (YFP) using gateway cloning system. The BiFC constructs along with positive control were introduced into plant cells through agro-infiltration. The non-florescent fragments of YFP tagged with HsfA1d produced no signal when they were infiltrated alone in tobacco leaves. The N and C termini of YFP fused with HsfA1d resulted in florescence upon co-expression in tobacco leaf epidermal cells. The intact YFP tagged with HsfA1d, after DAPI staining, was observed under 3 different laser beams of YFP, DAPI and merged. The same florescent signals detected under different channels of laser scanning confocal microscope confirmed the nuclear localization of HsfA1d. It is concluded, that HsfA1d is localized in the nucleus of cell.
Keywords: HsfA1d; subcellular localization; yellow florescent proteins; gateway cloning; BiFC